2001
DOI: 10.1046/j.1472-765x.2001.01004.x
|View full text |Cite
|
Sign up to set email alerts
|

The differential adherence capabilities of two Listeria monocytogenes strains in monoculture and multispecies biofilms as a function of temperature

Abstract: Aims: To determine the differential adherence capabilities at three different temperatures of Listeria monocytogenes Scott A, a clinical food pathogen, and L. monocytogenes FM876, a persistent strain from a milk-processing environment, to stainless steel. Methods and Results: Differential adherence was investigated by submerging stainless steel coupons in both 48-h Listeria monocultures and mixed cultures additionally containing Staphylococcus xylosus DP5H and Pseudomonas fragi ATCC 4973. Immuno¯uorescent micr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

9
59
0
2

Year Published

2003
2003
2015
2015

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 110 publications
(70 citation statements)
references
References 25 publications
9
59
0
2
Order By: Relevance
“…The type and the composition of food residue on foodprocessing equipment have been suggested to influence both the population levels of attached cells and their resistance to disinfectants (6,20,24,33,44). Moreover, in accordance with previous studies, attachment of L. monocytogenes was found to increase with increasing temperature (6,19,33,38). It has been suggested that these differences in attachment are independent of increases in cell density (33).…”
Section: Discussionsupporting
confidence: 71%
“…The type and the composition of food residue on foodprocessing equipment have been suggested to influence both the population levels of attached cells and their resistance to disinfectants (6,20,24,33,44). Moreover, in accordance with previous studies, attachment of L. monocytogenes was found to increase with increasing temperature (6,19,33,38). It has been suggested that these differences in attachment are independent of increases in cell density (33).…”
Section: Discussionsupporting
confidence: 71%
“…Previous research demonstrated that cell attachment and biofilm formation by L. monocytogenes are influenced by several factors, including characteristics of strains, physical and chemical properties of the substrate for attachment, growth phase of the bacteria, temperature, growth media, and the presence of other microorganisms (1,5,7,13,17,21,22,30). The properties of L. monocytogenes that make a strain persistent or nonpersistent in a food processing environment are not well understood.…”
mentioning
confidence: 99%
“…These microenvironments include variations in pH, nutrient concentrations, and oxygen levels (17,24). On a surface such as metal, biofilms allow for a variety of microorganisms with differing redox potential requirements to reside in close proximity.…”
mentioning
confidence: 99%
“…Temperature may have had an effect on the production of EPS, which is known to enhance the adherence capability of bacterial cells. SEM studies have shown that Listeria monocytogenes cells produced an EPS matrix at 21°C but not at 10 or 35°C (17). EPS is critical not only for initial adhesion but in the firm anchorage of bacteria to solid surfaces (17) and in the ability of biofilm microorganisms to deal with environmental stresses, such as nutrient limitations, solar radiation, and variations in temperature (20).…”
mentioning
confidence: 99%